- #1

n00by

- 7

- 0

## Homework Statement

Use the equivalence [itex]p\rightarrow(r \rightarrow s) \equiv p\wedge r\rightarrow s[/itex] to rewrite the following problem before the proof.

## Homework Equations

[itex][p\rightarrow (q\rightarrow r)]\wedge (p\rightarrow q) \tautologicallyimplies (p\rightarrow r)[/itex]

## The Attempt at a Solution

[itex][p\rightarrow (q\rightarrow r)]\wedge (p\rightarrow q) \tautologicallyimplies (p\rightarrow r)[/itex]

1. [itex]p\rightarrow (q\rightarrow r) \equiv p\wedge q \rightarrow r \equiv \neg p \vee \neg q \vee r[/itex]

2. [itex]p\rightarrow q \equiv \neg p \vee q[/itex]

3. [itex](\neg p \vee q)\wedge (\neg p \vee \neg q \vee r) \equiv ... \equiv p \rightarrow q\wedge r[/itex]

What am I doing wrong?

Thanks!